2018
DOI: 10.3389/fncel.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

It's All about Timing: The Involvement of Kir4.1 Channel Regulation in Acute Ischemic Stroke Pathology

Abstract: An acute ischemic stroke is characterized by the presence of a blood clot that limits blood flow to the brain resulting in subsequent neuronal loss. Acute stroke threatens neuronal survival, which relies heavily upon proper function of astrocytes. Neurons are more susceptible to cell death when an astrocyte is unable to carry out its normal functions in supporting the neuron in the area affected by the stroke (Rossi et al., 2007; Takano et al., 2009). For example, under normal conditions, astrocytes initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…There is a wealth of data and investigations demonstrating that energy restriction and accompanying spreading depolarization events are accompanied by a failure of extracellular K + -homeostasis in which astrocytes are critically involved [ 134 , 150 , 151 , 152 ]. A recent study also proposed an involvement of microglia in extracellular K + -homeostasis during spreading depolarisations [ 153 ].…”
Section: Relevance Of Astrocytic Cation Homeostasismentioning
confidence: 99%
“…There is a wealth of data and investigations demonstrating that energy restriction and accompanying spreading depolarization events are accompanied by a failure of extracellular K + -homeostasis in which astrocytes are critically involved [ 134 , 150 , 151 , 152 ]. A recent study also proposed an involvement of microglia in extracellular K + -homeostasis during spreading depolarisations [ 153 ].…”
Section: Relevance Of Astrocytic Cation Homeostasismentioning
confidence: 99%
“…In recent years, astrocytes have been found to function not only as neuronal support cells and neuroimmune cells but also as regulators that stabilize synapses (Codazzi et al, 2015 ; Murphy-Royal et al, 2015 ; Charvériat et al, 2017 ; van Deijk et al, 2017 ; Dubový et al, 2018 ; Milton and Smith, 2018 ). Barres and Smith ( 2001 ) found that including astrocytes in neuronal cultures, even as a feeder lay, can significantly increase synapse formation, and these synapses demonstrated normal postsynaptic potentials and frequency multiplication (Ullian et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The resultant increase of glutamate in the synaptic cleft resulting from K ir 4.1 inhibition results in abnormal modulation of synaptic transmission and network level communication [277,281] and is associated with the development and maintenance of neuroinflammation [282,283]. The pathological significance of K ir 4.1 downregulation in a neuroinflammatory environment is further emphasized by the results of several in vivo studies reporting reduced expression and/or function of this receptor in several neurodegenerative diseases, most notably multiple sclerosis and AD [284][285][286][287].…”
Section: Nutritional Ketosis Astrogliosis and K Ir 41 Functionmentioning
confidence: 99%
“…Hence, improvements in glutamate reuptake by astrocytes coupled with amelioration of glutamate dyshomeostasis, which may stem from nutritional ketosis would be expected to produce concomitant improvements in K ir 4.1-mediated astrocyte K + buffering. Increased levels of ATP fostered by the bioenergetic and metabolic consequences of induced ketosis may also be of therapeutic benefit as far as improving K + homeostasis mediated by K ir 4.1 is concerned as the optimum function of this receptor is also dependent on adequate levels of ATP [285,286,295,296]. Consequently, the documented improvements in oxidative stress, neuroinflammation, glutamate homeostasis, and ATP production in the CNS following prolonged ingestion of various KDs would be expected to result in beneficial effects on K ir 4.1 levels and function.…”
Section: Nutritional Ketosis Astrogliosis and K Ir 41 Functionmentioning
confidence: 99%